Reduction in severity and mortality in COVID-19 patients owing to heterologous third and fourth-dose vaccines during the periods of delta and omicron predominance in Thailand. (January 2023) - Intawong, Kannikar; Chariyalertsak, Suwat; Chalom, Kittipan; Wonghirundecha, Thanachol; Kowatcharakul, Woravut; Ayood, Pisittawoot; Thongprachum, Aksara; Chotirosniramit, Narain; Noppakun, Kajohnsak; Khwanngern, Krit; Teacharak, Worachet; Piamanant, Prapon; et al.
Highlights: The third vaccine dose reduced the risk of severe COVID-19 infection from the omicron variant. Optimal protection was observed with third dose administered 14-90 days before a positive test result. No severe COVID-19 outcomes or deaths were observed after the fourth vaccine dose. Boosters with BNT162b2, ChAdOx1, and messenger RNA-1273 offered similar protection. Abstract : Objectives: The COVID-19 pandemic has evolved quickly, with different variants of concern resulting in the need for countries to offer booster vaccinations. Although studies have assessed homologous schedules in detail, the effectiveness of heterologous booster vaccine schedules against severity and mortality with newer variants remains to be explored fully. Methods: Utilizing a Hospital Information System for COVID-19 established in Chiang Mai, Thailand, we conducted a cohort study by linking patient-level data on laboratory-confirmed COVID-19 cases to the national immunization records, during delta-predominant and omicron-predominant periods. Results: Compared to omicron, COVID-19 cases during the delta period were 10 times more likely to have severe outcomes and in-hospital deaths. During omicron, a third vaccine dose had an 89% reduced risk of both severe COVID-19 and death. The third dose received 14-90 days before the date of the positive test showed the highest protection (93%). Severe outcomes were not observed with the third dose during delta, and the fourth dose during the omicron period. All the vaccine types used for boosting in Thailand offered similar protection against severe COVID-19. Conclusion: Booster doses provided a very high level of protection against severe COVID-19 outcomes and deaths. Booster campaigns should focus on improving coverage by utilizing all available vaccines to ensure optimal protection.